Fresh banana leaves eaudiobook Healing indigenous landscapes through indigenous science. - Hernandez, Jessica (North Atlantic Books, 2022)
A 2022 Los Angeles Times Book Prize Finalist in Science & Technology An Indigenous environmental scientist breaks down why western conservationism isn't working—and offers Indigenous models informed by case studies, personal stories, and family histories that center the voices of Latin American women and land protectors. Despite the undeniable fact that Indigenous communities are among the most affected by climate devastation, Indigenous science is nowhere to be found in mainstream environmental policy or discourse. And while holistic land, water, and forest management practices born from millennia of Indigenous knowledge systems have much to teach all of us, Indigenous science has long been ignored, otherized, or perceived as "soft"—the product of a systematic, centuries-long campaign of racism, colonialism, extractive capitalism, and delegitimization. Here, Jessica Hernandez—Maya Ch'orti' and Zapotec environmental scientist and founder of environmental agency Piña Soul—introduces and contextualizes Indigenous environmental knowledge and proposes a vision of land stewardship that heals rather than displaces, that generates rather than destroys. She breaks down the failures of western-defined conservatism and shares alternatives, citing the restoration work of urban Indigenous people in Seattle; her family's fight against ecoterrorism in Latin America; and holistic land management approaches of Indigenous groups across the continent. Through case studies, historical overviews, and stories that center the voices and lived experiences of Indigenous Latin American women and land protectors, Hernandez makes the case that if we're to recover the health of our planet—for everyone—we need to stop the eco-colonialism ravaging Indigenous lands and restore our relationship with Earth to one of harmony and respect.